Quantification of State Financial Losses in Action Criminal Corruption: Approach Economic Analysis of Law and Its Implications for Effectiveness Criminalization - Ahmad Ferry Tanjung (JURNAL MERCATORIA, 2026)
Study This aim analyze quantification loss state finances in action criminal corruption with use approach analysis economy to law (economic analysis of law). The fundamental problems that often arise appear in practice enforcement law corruption is non-uniformity methodology calculation state losses by audit institutions such as the Audit Board Finance (BPK) and the Audit Board Finance and Development (BPKP), as well as the implications to proportionality criminalization. Research This use method juridical normative with approach conceptual, regulatory legislation, and studies case decision court. Research results show that approach analysis economy to law can become instrument effective in standardize method quantification state losses, so that criminalization can done in a way proportional and recovery - oriented loss (asset recovery). Research This recommend integration principles economy in policy law criminal corruption in order to achieve effect optimal deterrence without sacrifice certainty law and justice substantive.